THE MINDSET OF SUNDANESE PEOPLE IN THEIR LANGUAGE EXPRESSIONS - Sudaryat, Yayat (Indonesian Journal of Applied Linguistics, 2015)
This study is aimed at describing the mindset of Sundanese people in their language expressions examined from psycho-pragmatic aspects. The description is connected to Sundanese language as the reflection of mindset, the cognitive system, and Sundanese peopleâ€™s way of thinking in Sundanese language expressions. The study applied descriptive method. To collect data, textual technique (literary study), intuitive technique (introspection), and elicitation technique were used. The result of the study shows that Sundanese language phenomenon, which is the reflection of mindset is seen from its sound accord, contradiction, kirata basa (language prediction), abbreviation, and language paradigm. The cognitive system of Sundanese language is related to naming system (of people, of body parts, of places or toponymy), time, numbers, colors, and environment. Sundanese peopleâ€™s way of thinking refers to outspokenness, subjectivity, state of being substantial, state of being humorous, state of being emotional, indirectness, indistinctness, politeness, sensitivity, and loyalty.Â